2016
DOI: 10.3354/dao02987
|View full text |Cite
|
Sign up to set email alerts
|

ORF13 in the Type III secretion system gene cluster of Edwardsiella tarda binds to the mammalian factor Cugbp2

Abstract: The Type III secretion system (TTSS) is essential for the intracellular replication of Edwardsiella tarda in phagocytes of fish and mammals, and a hypothetical gene (orf13) located in the TTSS gene cluster is required for intracellular replication and virulence of E. tarda. Here, we show that under TTSS-inducing conditions, the protein ORF13 was secreted into culture supernatant. Then, using a yeast 2-hybrid screen, we show that the mammalian factor Cugbp2, which regulates apoptosis in breast cancer cells, dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Unexpectedly, our previous study revealed that EscE can be secreted and translocated in a T3SS-dependent manner, and it regulates the secretion of the T3SS proteins according to its own steady-state protein level inside E. piscicida ( 28 ). Accordingly, it was verified that EscE (Orf13) is secreted and directly interacts with mammalian factor Cugbp2 upon its translocation ( 29 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Unexpectedly, our previous study revealed that EscE can be secreted and translocated in a T3SS-dependent manner, and it regulates the secretion of the T3SS proteins according to its own steady-state protein level inside E. piscicida ( 28 ). Accordingly, it was verified that EscE (Orf13) is secreted and directly interacts with mammalian factor Cugbp2 upon its translocation ( 29 ).…”
Section: Resultsmentioning
confidence: 97%
“…EscE is required to stabilize EsaH, and it can be secreted through the T3SS ( 28 , 29 ). But will EsaH also be secreted upon secretion of EscE?…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations